Yield and composition of rosemary essential oil cultivated with different doses of nitrogen and sulfur - Souza, Aline dos Anjos; Santos, Anacleto Ranulfo dos; Souza, Girlene Santos de; Alves, Pericles Barreto; Oliveira, Uasley Caldas de; Cardoso Alves, Aglair (Comunicata Scientiae, 2024)
Essential oils have great commercial importance for the pharmaceutical, cosmetic and food industries. Because they have therapeutic, flavoring and antioxidant properties, due to their active principles. Studies on the form of cultivation, as well as fertilization management are necessary, since information related to the production of secondary metabolites is still insufficient. Thus, the objective of this work was to evaluate the yield, content and composition of rosemary essential oil cultivated with different concentrations of nitrogen and sulfur in the soil. The treatments were distributed in a 4x2 factorial scheme with four nitrogen doses: 105, 210, 315 and 420 mg dm3, combined with two sulfur doses: 32 and 64 mg dm3 and with seven replications, totaling 56 experimental units. According to the results obtained, the combination of doses 420 of N and 64 S provided the best contents and yield of rosemary essential oil. a-pinene and 1,8-cineole had the highest concentrations for all treatments studied, with about 85% to 95% of the total constituents of the oils.